What is the Role of Kinesiophobia and Pain Catastrophizing in Outcomes After Hip Arthroscopy for Femoroacetabular Impingement Syndrome? - Ian M. Clapp, B.A; Benedict U. Nwachukwu, M.D., M.B.A; Edward C. Beck, M.D., M.P.H; Jonathan P. Rasio, B.S; Thomas Alter, M.S; Bradley Allison, P.T., D.P.T., O.C.S; Shane J. Nho, M.D., M.S (Elsevier, 2020)
Purpose: To (1) investigate trends in kinesiophobia and pain catastrophizing after hip arthroscopy for femoroacetabular impingement syndrome (FAIS), and (2) determine whether kinesiophobia and pain catastrophizing scores are associated with achieving minimal clinically important difference (MCID) for any of the hip-specific patient-reported outcome questionnaires. Methods: Patients undergoing primary hip arthroscopy for treatment of FAIS between December 2016 and March 2017 were prospectively enrolled. Patients received the Tampa Scale of Kinesiophoibia-11 (TSK-11) and Pain Catastrophizing Scale (PCS) questionnaires preoperatively, 6 months, and 1 year postoperatively. They also received the hip-specific patient-reported outcome questionnaires (Hip Outcome Score Activities of Daily Living and Sport-Specific subscales, modified Harris Hip Score, and International Hip Outcome Tool-12), as well as visual analog scale for satisfaction and pain preoperatively and 1-year postoperatively. The threshold for achieving MCID was determined for each hip outcome tool, and patients achieving MCID were compared with those who did not. Results: A total of 85 (80.2%) patients (mean age: 33.7 ± 12.4 years; female: 75.3%) were included in the final analysis. At 1-year follow-up, there was a significant reduction in TSK-11 scores (26.22 ± 5.99 to 18.70 ± 6.49; P < .001) and PCS scores (17.81 ± 10.13 to 4.77 ± 7.57; P < .001) when compared with preoperative scores. 1-year PCS scores were significantly lower in patients achieving MCID compared with patients failing to achieve MCID (3.2 ± 4.4 vs 10.8 ± 15.2; P = .006). There were no significant differences in TSK-11 scores between those achieving and not achieving MCID. Conclusions: Patient kinesiophobia and pain catastrophizing both show significant improvements 1 year after undergoing hip arthroscopy for FAIS. However, pain catastrophizing scores at 1 year are significantly greater in patients not achieving MCID, whereas no association was identified between kinesiophobia and likelihood for MCID achievement. This suggests PCS may be a more useful tool than TSK-11 during postoperative rehabilitation for identifying patients at risk for not achieving MCID. Level of Evidence: Level II, prospective case series